PENGARUH PERSEPSI, MOTIVASI, BREVET PAJAK, DAN PERAN ORANG TUA TERHADAP MINAT BERKARIR DALAM BIDANG PERPAJAKAN: (Studi Kasus Pada Mahasiswa Jurusan Akuntansi Universitas Islam Syekh-Yusuf) - Mahabah, Siti Aenun; Safitriawati, Tita; Dhahana, Sat Yudha (Desanta Publisher, 2025)
This study aims to determine the effect of perception, motivation, tax brevet, and the role of parents on career interest in taxation. In this study, the method used is the quantitative method. Data collection using a questionnaire distributed via Google Form. The sample used was 74 respondents of accounting students of Syekh-Yusuf Islamic University who were determined using the Slovin formula with the purposive sampling technique as a sampling technique. And the data obtained is processed and tested using the SPSS (Statistical Package for Social Sciences) software program version 25. The research results in this study prove that the perception variable affects career interest in taxation. Motivation variables affect career interest in taxation. The tax brevet variable has no effect on career interest in taxation. The variable role of parents has no effect on career interest in taxation. And testing simultaneously the variables of perception, motivation, tax brevet, and the role of parents affects career interest in taxation.